Differential rates of induced abortion in Spain: educational attainment and age among native and immigrant women - Miguel Requena; Mikolaj Stanek (Elsevier, 2024)
Objective: Analyzing the variations in induced abortion (IA) rates across different subpopulations in Spain based on country of origin, while considering educational and age composition. Method: Using 2021 Voluntary Termination of Pregnancy register and 2021 Spanish Census microdata, we calculated crude IA rates and age-specific abortion rates. We used age-standardized IA rates (ASIAR) to account for the confounding effect of age composition. We compared seven subpopulations residing in Spain, taking into account simple ages and educational levels aggregated into four categories. Results: Immigrant women, especially those from Sub-Saharan and Latin American countries, consistently had higher IA rates compared to native Spanish women. According to age-specific IA rates, university-educated women had considerably fewer abortions than women with other education levels at any age. Age-standardized rates stratified by migratory origin revealed that native Spanish women with primary education or less had higher IA rates than their immigrant counterparts. There was a clear non-linear, association between educational level and IA rates among immigrants. The highest propensity for IA was found among secondary school graduates, while university graduates had the lowest IA rate. Conclusions: The study demonstrated that variability in sociodemographic characteristics had an impact on IA rates. Young women with middle educational attainment and immigrant background had a higher likelihood of undergoing IA in Spain. The relationship between educational level and IA rates was complex, with variations observed among different groups and changes over time. Resumen: Objetivo: Analizar las variaciones en las tasas de aborto inducido (AI) en diferentes subpoblaciones en España según el país de origen y considerando la composición por edad y educación. Método: Utilizando el Registro de Interrupción Voluntaria del Embarazo de 2021 y el censo español de 2021, se calcularon las tasas brutas de AI y las tasas específicas por edad para diferentes subgrupos, así como las tasas de AI estandarizadas por edad para tener en cuenta el efecto confusor de la composición por edad. Se compararon siete subpoblaciones residentes en España, teniendo en cuenta la edad y el nivel educativo agregado en cuatro categorías. Resultados: Las mujeres inmigrantes, en especial las provenientes de países subsaharianos y latinoamericanos, tenían tasas de AI consistentemente más altas que las mujeres españolas. Las tasas específicas por edad revelaron que las mujeres con educación universitaria tuvieron considerablemente menos AI en todas las edades que las mujeres con niveles educativos inferiores. Sin embargo, estas tasas variaban entre los diferentes grupos de mujeres inmigrantes. Las tasas estandarizadas por edad y estratificadas por origen migratorio revelaron que las mujeres españolas con educación primaria o inferior tenían tasas más altas de AI que las mujeres inmigrantes con el mismo nivel educativo. Entre las inmigrantes, se observó una clara asociación no lineal entre el nivel educativo y las tasas de AI: la mayor propensión al AI se encontró entre las tituladas de educación secundaria, mientras que las graduadas universitarias tuvieron la tasa de AI más baja. Conclusiones: El estudio demostró que la variabilidad en las características sociodemográficas de los grupos tuvo su impacto en las tasas de AI. Las mujeres jóvenes españolas con menor nivel educativo y las inmigrantes tuvieron una mayor probabilidad de someterse a AI en España. La relación entre el nivel educativo y las tasas de AI es compleja, con variaciones observadas entre diferentes grupos y cambios a lo largo del tiempo.